THE IMPACT OF ENTREPRENEURIAL SPIRIT ON FIRM PERFORMANCE: A PILOT STUDY ON MEDIATING EFFECTS USING SPSS ANALYSIS - Ding, Yali; Ibrahim, Muhammad Azman; Shobri, Diyana Mohammed (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
The research investigates the interplay between entrepreneurial spirit, dynamic marketing capabilities, and firm performance. Prior to initiating large-scale data collection, a pilot study was carried out to assess the questionnaire's reliability and validity. Online questionnaires were disseminated to the owners and managers of small and medium - sized manufacturing enterprises, and ultimately, 64 valid samples were obtained. The collected data was analyzed by means of descriptive, correlation, regression, and mediation effect analyses using SPSS20.0 software. The main discovery indicates that dynamic marketing capabilities act as a mediator in the relationship between entrepreneurial spirit and firm performance. This research offers a preliminary foundation for comprehending these relationships, serves as groundwork for large-scale studies, and enriches relevant theories to offer guidance for corporate decision-making and operations.